Colorectal cancer in hereditary breast cancer kindreds - Lin, Kevin M.; Ternent, Charles A.; Adams, Dean R.; Thorson, Alan G.; Blatchford, Garnet J.; Christensen, Mark A.; Watson, Patrice; Lynch, Henry T. (Diseases of the colon & rectum, 1999)
This study compared characteristics of colorectal cancer between families with dominant breast cancer inheritance and the general population. The cumulative incidence of colorectal cancer was also studied in genetically determined breast cancer syndrome subjects with BRCA1 and BRCA2 mutations and compared with the general population. Subjects included 42 patients with colorectal cancer from 32 clinically determined hereditary breast cancer kindreds based on the autosomal dominant inheritance of breast cancers and early age of onset. The general population colorectal cancer cohort was composed of 755 patients from a tumor registry. Lifetime risk of colorectal cancer was determined in 164 BRCA1 and 88 BRCA2 gene mutation carriers and compared with the general population. Mean age of colorectal cancer onset, anatomic site distribution, histologic stage at presentation, and five year stage-stratified survival rates were compared between clinically determined hereditary breast cancer family members and the general population. The lifetime risk of colorectal cancer in male BRCA1 and BRCA2 mutation carriers was 5.6 percent, which was not different from 6 percent in males from the general population. Likewise, the lifetime colorectal cancer risk in female BRCA1 and BRCA2 mutation carriers was 3.2 percent, which was not different from 5.9 percent in females from the general population. Mean age of onset +/- standard error for patients with colorectal cancer was 60 +/- 2 years for hereditary breast cancer kindreds compared with 67 +/- 0.4 years for the general population (P = 0.0004). Colorectal cancer site distribution did not vary between hereditary breast cancer and the general population. Overall colorectal cancer stage distribution was significantly different, with more Stage I and fewer Stage IV cancers in subjects with hereditary breast cancer compared with the general population (P = 0.01). Overall five year stage-stratified colorectal cancer survival rate +/- standard error was 66 +/- 8 percent for hereditary breast cancer kindreds and 46 +/- 2 percent for the general population (P = 0.023). Lifetime cumulative colorectal cancer incidence in subjects with BRCA1 and BRCA2 gene mutations was not different from the general population. However, significant differences in colorectal cancer were noted between hereditary breast cancer family members and the general population. Hereditary breast cancer-associated colorectal cancer had an earlier age of onset, lower tumor stage, and better survival rate than the general population. Except for age of onset, colorectal cancer in hereditary breast cancer kindreds exhibited more favorable characteristics than colorectal cancer in the general population.